Determinants of Customer Attitude Towards Green Marketing - A. U. Mani, Umma; N. Ndubuisi, Veronica (British Journal of Marketing Studies, 2023)
This is a conceptual paper that tries to bring out the relationship between marketing discipline, the natural environment and customers attitude. The notion of marketing is too vast therefore, the paper concentrated on the external dimensions of green marketing at strategic and tactical level aim to reach the consumers. Therefore, the ‘4ps’ traditional marketing mix variables use in an innovative manner will be used as the yardstick to measure the green marketing in this paper. Nigeria is still in its infant stage on the green concept. Nigeria ranked 100th scoring 54.76 out of 180 countries for overall environmental performance 1 which could be due to non-challenge attitude among Nigerian consumers and marketing professionals towards the environment. Therefore, this paper aim at proposing a research model that will determine customer attitude towards green marketing. Three probable factors were identified and propose in the research model that will determine the relative contributions of customers’ cognitive, conative and affective senses on their overall attitude towards the green marketing mix variables (green: products; price; promotion and place). Structured questionnaire is proposed to be sent to 524 lecturers and researchers of University of Maiduguri whom will be selected by stratified random sampling. Data will be collected online through monkey survey. Multiple regressions using SPSS will be employed to test the hypotheses postulated. It is expected that findings will provide empirical evidence on the influence and contributions of the attitude components as determinants of overall customer attitude towards green marketing which could provide informative insights on consumers’ propensity to consume which could provide basis for decision making for the policy makers, current and potential green marketers and consumers.